The impact of non-traditional banking activities on the risk & profitability of domestic Singapore banks. - Chen, Christine Siew Mei. (2009)
This project examines the impact of non-traditional banking activities on the profitability and risk of domestic Singapore banks over the period 1991-1996. For the purpose of this study, non-traditional banking activities are defined as activities which generate non-interest income for a banking organisation, that is, activities outside of traditional bank lending.